2007
DOI: 10.1038/sj.mt.6300076
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Oncolytic Measles Virus to Circumvent the Intracellular Innate Immune Response

Abstract: The innate antiviral responses of tumor cells are often impaired but may still be sufficient to impede the intratumoral spread of an oncolytic virus. Here, we establish that the oncolytic measles virus (MV-eGFP) induces interferon (IFN) production in human myeloma and ovarian cancer cells. In addition, MV gene expression and virus progeny production were inhibited by IFN treatment of these tumor cells. The P gene of wild-type measles virus encodes P/V/C proteins known to antagonize IFN induction and/or respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 43 publications
1
77
0
1
Order By: Relevance
“…Regardless of the mechanism of selective targeting, all oncolytic viruses must also overcome the arsenal of antiviral programs that the individual cell has at its disposal to resist infection and/or the spread of viruses. One strategy to generate a more potent OV is to arm the virus with genes that express products to circumvent or blunt the innate antiviral response of the individual cell (10,11). A different approach is to engineer viruses that are unable to resist cellular antiviral programs (8,41), thus increasing their safety profile because they cannot replicate in normal tissues but retain the ability to grow in malignant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the mechanism of selective targeting, all oncolytic viruses must also overcome the arsenal of antiviral programs that the individual cell has at its disposal to resist infection and/or the spread of viruses. One strategy to generate a more potent OV is to arm the virus with genes that express products to circumvent or blunt the innate antiviral response of the individual cell (10,11). A different approach is to engineer viruses that are unable to resist cellular antiviral programs (8,41), thus increasing their safety profile because they cannot replicate in normal tissues but retain the ability to grow in malignant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although aberrations in the cellular antiviral response occur frequently in tumors, the magnitude of the defect is quite variable and can be a barrier to effective OV spread through a malignancy (7)(8)(9). Indeed more potent OVs are being developed that express viral gene products to combat cellular innate immune responses (10,11); however, this genetic approach may ultimately limit the safety of the therapeutic. We reasoned that combining a viral therapeutic with a compound that reversibly compromises host antiviral genetic programs could provide a means to enhance OV growth in tumor cells.…”
Section: Hdac Inhibitor ͉ Oncolytic Virus ͉ Refractory Tumors ͉ Combimentioning
confidence: 99%
“…In addition, Haralambieva et al 9 showed that measles virus-induced gene expression and intratumoral virus spread is inhibited by IFN, which is triggered by virus infection of tumor cells. Interestingly, currently available oncolytic measles viruses are derived from Edmonston tag (Edmtag) strain, which has lost most of the IFNantagonizing activities.…”
Section: Suppression Of Innate Immune Response Enhances Efficacymentioning
confidence: 99%
“…Edmtag-based measles virus engineered to express the measles phosphoprotein (P) gene products (P/V/C proteins) from wild-type measles virus, known to antagonize IFN induction and response, exhibited reduced IFN sensitivity and a reduced IFN induction in lymphoma, myeloma and activated peripheral blood mononuclear cells (PBMC). 9 Measles virus encoding the P gene products also showed significantly enhanced systemic efficacy in a myeloma xenograft model. This study highlights the importance of innate antiviral responses of tumor cells that need to be considered when designing oncolytic viruses.…”
Section: Suppression Of Innate Immune Response Enhances Efficacymentioning
confidence: 99%
“…The attenuation of OV growth in normal tissues is often due to the inability of OVs to antagonize normal cellular, interferon (IFN)-mediated antiviral responses. Many tumour cells have acquired defects in their IFN response during their malignant evolution, and are correspondingly excellent hosts for OV growth [3][4][5][6][7] . However, the extent of the IFN response deficit in cancers is highly variable and can impair the efficacy of OV therapies 8 .…”
mentioning
confidence: 99%